Food Security in Bangladesh: Present Status and Trend (Progressive Agriculture, 2014)
The study was is an attempt that offers better understanding the overall trend and pattern of food consumption and micro-nutrient intake using secondary data. The study revealed that total dietary energy consumption was 2230 kcal/capita/day which was higher than the total energy requirements of 2225 kcal/capita/day in 2003-2005. The shares of energy from protein (8.61%) and from fat (10.90%) were lower than 12% and 20% respectively, although upward trends for dietary fat and protein consumption were observed in between 1969-1971 and 2003-2005. The prevalence of child malnutrition declined in between 1992 and 2006. The results indicate that Bangladesh is not currently food secure in the sense of share of the total energy coming from protein and fat.DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19178 Progress. Agric. 24(1&2): 263 - 271, 2013